PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KOMITMEN ORGANISASI (Survai Pada Pengurus Yayasan Thariq Bin Ziyad Bekasi 2021) - Cucu Sugiarti (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
The Tariq Bin Ziyad Foundation Bekasi is one of the educational institutions that was established in 1997. The Tariq Bin Ziyad Foundation Bekasi has the duties and responsibilities of planning, formulating programs and organizational regulations. In addition, it has a role in organizing the structure under it, starting from PAUD/TK, SDIT, SMPIT, SMAIT and Boarding School levels. The number of population and this sample has the same number in a small capacity, namely only 41 people through the distribution of google forms to each of these respondents. To find out the sample size in this study, it was determined by categorizing all the governing bodies of the Tariq Bin Ziyad Foundation. The results of this study are simultaneously leadership style and motivation have a very positive and significant effect on organizational commitment.